Convective heat transfer of cattaneo-christov heat flux model over a wedge / Muhammad Solleh Asmadi - Muhammad Solleh , Asmadi (2019)
The convective boundary layer flow, heat and mass transfer of Cattaneo-Christov heat flux model over a wedge is investigated. The heat transfer of two-dimensional, steady, incompressible laminar flow of upper-convected Maxwell fluid and Carreau fluid past a horizontal plate and a horizontal wedge are studied by using Cattaneo-Christov heat flux model. The mathematical formulation of the governed equation is presented. Similarity transformation for local similarity solution is used to reduce the partial differential equations to nonlinear ordinary differential equations. The resulting nonlinear ordinary differential equations are solved numerically using second-order and third-order finite difference method. Comparisons of present result with previously published results are done and they are found to be in good agreement. The numerical values of local skin friction coefficient, local Nusselt number and local Sherwood number are tabulated. The effects of local Deborah number, Weissenberg number, wedge angle parameter, power-law index, Prandtl number, Schmidt number, suction parameter, heat generation/absorption parameter, heat radiation parameter and chemical reaction parameter on the fluid velocity, temperature and concentration profiles are presented graphically and discussed in details. Several dimensional forms of the system are provided and the heat map of the thermal boundary layer with different parameters are analysed.